Study on axial compressive properties of CFRP-confined ultra-high toughness cementitious composites - Ban Li; Huang-kai Sun (PLoS ONE, 2025)
In order to study the mechanical properties of carbon fiber reinforced polymer (CFRP)-confined ultra-high toughness cementitious composites (UHTCC) under axial compression load, the preparation of UHTCC and the treatment of CFRP confinement were completed according to the specifications, considering the influence of single fiber types and CFRP confinement layers. After the axial compression load failure test, the failure phenomenon and stress-strain curves of the test were obtained. The influence mechanism of different single fiber types and different CFRP confinement layer on the axial compressive properties of CFRP-confined UHTCC was analyzed, and the stress-strain curves of the test was compared with the existing stress-strain models. The research results show that the ultimate compressive strength of UHTCC with steel fibers is significantly improved, reaching 84.6 MPa (compared to 27.6 MPa for unconfined specimens); The ultimate strain of UHTCC with PVA or PE increased significantly, with an increase of 107.6% and 243.2% respectively compared to unconfined specimens. The deviation between the calculated results of the Samaam model and the experimental results is less than 10%, indicating that the use of the Samaam model to propose a mathematical model for the stress-strain of CFRP-confined UHTCC is feasible.